1999
DOI: 10.1002/(sici)1098-2388(199912)17:4<230::aid-ssu3>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Surgery versus surveillance in stage I non-seminoma testicular cancer

Abstract: Today, the standard treatment for patients with clinical Stage I non‐seminomatous testicular germ cell tumors (NSTGCT) following orchidectomy is either primary retroperitoneal lymph node dissection (RPLND) or close surveillance with cisplatin‐based polychemotherapy in case of a relapse. Both treatment modalities provide excellent overall survival rates up to 100%. Consequently, selection of the most appropriate management option is not primarily guided by survival considerations. The choice between the availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
3
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 83 publications
(147 reference statements)
2
3
0
Order By: Relevance
“…Presence of embryonal carcinoma is also associated with poorer relapse-free survival. This is in line with previous knowledge which unequivocally support the predictive value of vascular invasion assessment in nonseminoma patients [5,12,[36][37][38][39][40][41][42][43][44][45][46] and further suggest amount of embryonal carcinoma as adjunctive in this context [5]. For seminoma, however, other variables are advanced to help in clinical decision-making: tumor size and rete testis invasion.…”
Section: Discussionsupporting
confidence: 88%
“…Presence of embryonal carcinoma is also associated with poorer relapse-free survival. This is in line with previous knowledge which unequivocally support the predictive value of vascular invasion assessment in nonseminoma patients [5,12,[36][37][38][39][40][41][42][43][44][45][46] and further suggest amount of embryonal carcinoma as adjunctive in this context [5]. For seminoma, however, other variables are advanced to help in clinical decision-making: tumor size and rete testis invasion.…”
Section: Discussionsupporting
confidence: 88%
“…Specifically, the aim is to better discriminate those patients who truly benefit from further treatment after orchiectomy from those who can safely follow a surveillance protocol. 6,37,38 The most consistent histological parameter to predict disease recurrence in clinical stage I nonseminoma has been vascular invasion, [11][12][13][14][15][16][17][18][19][20][21][22][23] and our study was no exception, with vascular invasion being the only variable with significant impact on relapsefree survival after multivariable analysis. 39,40 However, more factors apart from vascular invasion have been collected that demonstrate an impact in determining disease relapse, namely the amount of embryonal carcinoma.…”
Section: Discussionsupporting
confidence: 54%
“…7,8 Vascular invasion has been pointed out as such a marker in various studies, an idea first suggested by Raghavan et al 9 and Peckam et al 10 The presence of vascular invasion is associated with poor prognosis, relapse, and metastases, particularly in nonseminomas. 5,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] The relevance of vascular invasion in testicular germ cell tumors is illustrated by its inclusion in the TNM staging system, resulting in a pT2. 26 Given this clinical importance, strict criteria for establishing the diagnosis of vascular invasion are recommended by expert panels, as some representations may result in overdiagnosis and, hence, possible overtreatment of patients.…”
mentioning
confidence: 99%
“…In a large study, 15% of patients with a negative lymph node dissection experienced recurrence, usually pulmonary and usually within 18 months [22]. The overall survival rate of patients with pathological stage I is about 99% [23].…”
Section: Nerve-sparing Retroperitoneal Lymph Node Dissectionmentioning
confidence: 99%
“…Prognostic factors for patients with stage I disease that may predict the likelihood of occult metastases are the presence of lymphatic or venous invasion in the primary tumour, the presence of embryonal cell carcinoma and the absence of yolk sac elements in the primary tumour [23]. A more sophisticated way to stain proliferating tumour cells in testicular tumours with a monoclonal antibody MIB-1 against Ki-67 in combination with the volume of embryonal cell carcinoma and the transaxial diameter of retroperitoneal lymph nodes in the predicted landing zone allows a low-risk clinical stage I classification [25].…”
Section: Nerve-sparing Retroperitoneal Lymph Node Dissectionmentioning
confidence: 99%